Prevalence of Intestinal Protozoa Infections and Associated Risk Factors among Preschool Aged Children in Mkuranga District, Tanzania: A Community Based Cross-Sectional Study (Tanzania Medical Journal, 2021)
BackgroundIntestinal protozoa infections are among the public health concern in children and can lead to considerable morbidities such as growth retardation, anemia, nutrition deficiency, physical weakness and mental health problems. In Tanzania, there is a paucity of data on intestinal protozoa infections among preschool aged children (PSAC).Broad objectiveThis study aimed to determine the prevalence of intestinal protozoa infections among PSAC and associated risk factors in Mkuranga district, Tanzania.MethodologyA community based cross-sectional study was conducted between April and June 2019 to determine the prevalence of intestinal protozoa. Stool samples were collected from PSAC and processed using formal-ether concentration method. Risk factors were identified using questionnaire and checklist. Data were entered and analysed by using Statistical Package for the Social Sciences software version 20. Univariate and multivariate logistic regressions were performed to determine association between prevalence of intestinal protozoa and socio-economic, water source, hygiene and sanitation variables.ResultsA total of 20 (3.8%) children were infected with intestinal protozoa (Entamoeba coli or Giardia lamblia). We found the increased risk of intestinal protozoa infections with increased age of children (AOR = 1.07, p = 0.045). Also, we observed a reduced odds of intestinal protozoa infections among PSAC living in low populated households (AOR 1-5/11+ = 0.14, p = 0.016 and AOR 6-10/11+= 0.10, p = 0.008), using non-spring water (AOR protected well/spring = 0.011, p = 0.023), (AOR bore hole/spring/spring = 0.008, p = 0.006), (AOR tap away of home/spring = 0.013, p = 0.014) and (AOR tape at home/spring = 0.006, p = 0.011)) and raised by young and middle-aged parents/guardian (AOR young/older = 0.20, p = 0.042 and AOR middle-aged/older = 0.18, p = 0.047).ConclusionThere was a low prevalence of intestinal protozoa infection among PSAC in the two communities studied. Despite low prevalence of intestinal protozoa, the transmission is present hence the need to initiate control measures. Health education should be provided to parents/guardians on protecting water sources, treatment of drinking water and supervision of latrine usage by PSAC and introduction of hand washing facilities are crucial.Key words: Intestinal protozoa, Preschool aged children, Mkuranga and Tanzania.